Asuhan Kebidanan Pada Ibu Pasca Persalinan Di PMB Nelly Suryani Wilayah Kerja Puskesmas Kuok - Dwi Mawardi, Nira; Apriyanti, Fitri (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Postpartum is a critical period where a series of changes occur in the mother which have physical, psychological and social impacts. To optimize the health of mother and baby, postnatal care must be an ongoing process, with care and support tailored to the needs of each postpartum mother so that the care provided can help the mother through the postpartum period. Postnatal care consists of monitoring and examination. Examination materials include measuring the body temperature and pulse of the birthing mother, recording blood pressure, examining the breasts, assessing uterine involution, monitoring lochea. The aim of this case is to determine the midwifery care given to Mrs. U aged 19 years P1A0H1, good changes from day to day, at 6 (six) hours after delivery the mother complained of pain in the stitched wound area, on the 6th (sixth) day the mother still feel pain in the stitched wound area, at the 2nd (second) week the mother starts to feel no pain in the stitched wound area, and at the 6th (sixth) week the mother no longer feels pain in the stitched wound area. From the results of this research, it is hoped that postpartum mothers will always maintain proper perineal hygiene. In this way, the care given to the patient went well.